Chemical attributes of a savannah Typic Hapludox soil under management systems - doi: 10.4025/actasciagron.v33i3.6593 - Muraishi, Cid Tacaoca; Alves, Marlene Cristina; Silva Júnior, Aparecido da; Souza, Zigomar Menezes de (Acta Scientiarum. Agronomy, 2011)
This study was conducted at the Experimental Station belonging to UNESP Engineering University, Ilha Solteira Campus, based in Selvíria, Mato Grosso do Sul State, Brazil, with the aim of evaluating chemical alterations in an Oxisol after being managed for two years with organic and/or chemical fertilization and different tillage systems during the agricultural years of 2004/2005 and 2005/2006. The treatments were: conventional-tillage; chisel tillage and no-tillage; the fertilization treatments were: control (no fertilization); chemical fertilization (300 kg ha-1 from the 20-00-20); organic fertilization (cattle manure - 20 Mg ha-1); organic + ½ the recommended chemical fertilization for the used crop; 20 and 30 Mg ha-1 of sewage sludge. Soybean was used in the first year and sorghum in the next year, evaluating the soil chemical attributes in four layers. The soil chemical attributes were changed in the first year; the organic fertilization, sewage sludge and organic+chemical fertilization were efficient to change the chemical attributes; the sewage sludge was more efficient in soil P recuperation and, the no-tillage system contributed to soil K increase.